Microeconomic Consequences and Macroeconomic Causes of Foreign Direct Investment in Southern African Economies - Lederman, Daniel; Mengistae, Taye; Xu, Lixin Colin (Taylor and Francis, 2013)
The authors use a new data set on firms in 13 countries of the Southern African Development Community (SADC) and comparators from other regions to identify the benefits and determinants of FDI in this region. Foreign Direct Investment (FDI) has facilitated local development in the SADC. Foreign-owned firms perform better than domestic firms, are larger, and locate in richer and better-governed countries and in countries with more competitive financial intermediaries. They are also more likely to export than domestic firms and evidence suggests that they might have positive spillover effects on domestic firms. Based on a standard empirical model, the SADC is attracting the inward FDI per capita that the region's level of income would predict. But this means that there are less capital inflows per capita to the region than there are to wealthier parts of the developing world. Moreover, the SADC is attracting less FDI than comparators for reasons that are possibly more fundamental than current income, namely, countries’ past growth record, demographic structure and the quality of physical infrastructure. Interestingly, inward FDI is less sensitive to variation in income within the SADC than in other parts of the world, but is more responsive to changes in country's openness to trade.